Leveraging Large Language Models for Enhancing Safety in Maritime Operations - Tymoteusz Miller; Irmina Durlik; Ewelina Kostecka; Adrianna Łobodzińska; Kinga Łazuga; Polina Kozlovska (Applied Sciences)
Maritime operations play a critical role in global trade but face persistent safety challenges due to human error, environmental factors, and operational complexities. This review explores the transformative potential of Large Language Models (LLMs) in enhancing maritime safety through improved communication, decision-making, and compliance. Specific applications include multilingual communication for international crews, automated reporting, interactive training, and real-time risk assessment. While LLMs offer innovative solutions, challenges such as data privacy, integration, and ethical considerations must be addressed. This review concludes with actionable recommendations and insights for leveraging LLMs to build safer and more resilient maritime systems.